Intelligent systems of computing and informatics - Shamsul Ariffin Abdul Karim; Kulkarni, J.Anand; On, Kim Chin; Mohd Hanafi Ahmad Hijazi (Boca Raton, FL : CRC Press, 2024)
'This book aims to develop a new Intelligent Systems of Computing and Informatics (ISCI) to cater to the needs of industries in line with the United Nation Sustainable Development Goals (SDGs) of affordable and clean energy and sustainable cities and communities'--
Includes bibliographical references and index.
Keywords: Expert systems (Computer science)